FAKTOR-FAKTOR PENGHAMBAT PELAKSANAAN PROGRAM PENGAYAAN PADA MATA PELAJARAN IPS DI SMK - Sari, Lusi Linda; Pitoewas, Berchah; Yanzi, Hermi (Jurnal Kultur Demokrasi, 2015)
The objective of this research was to describe and to analyze the inhibiting factors of enrichment program implemention on social subject at SMKN 2 Bandar Lampung.This research used qualitative descriptive method with the number of population were 8 respondents. The data collecting techniques that used were questionnaire, interview,Â  and document. On the other hand, the data analysis that used was interval and percentage formula. Based on the data, it showed that: (1) The factor of teachersâ competence in understanding the enrichment are two respondents orÂ  25 % included in fairly good understanding category. (2)The factor of teacherâs competence in giving enrichment program to 5 respondents or 62.5 % included in poor understanding category, (3) The factor of teacherâs competence in developing are information technology and communication, were 5 respondents or 62.5 % included in fair understanding category, (4) In timing factor,Â  there were 4 respondents or 50 % included in less effective category.Tujuan penelitian untuk menjelaskan dan menganalisis faktor-faktor penghambat pelaksanaan program pengayaan pada mata pelajaran IPS di SMK Negeri 2 Bandar Lampung. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif dengan jumlah populasi 8 responden. Teknik pengumpulan data yang digunakan adalah angket, wawancara dan dokumentasi, sedangkan analisis data menggunakan rumus interval dan presentase. Berdasarkan hasil penelitian menunjukan bahwa: (1) Faktor kemampuan guru memahami program pengayaan sebanyak 2 responden atau 25% masuk dalam kategori cukup memahami, (2) faktor kemampuan guru memberikan kegiatan pengayaan sebanyak 5 responden atau 62,5% masuk Â dalam kategori kurang mampu, (3) faktor kemampuan guru mengembangkan teknologi informasi dan komunikasi sebanyak 5 responden atau 62,5 % masuk dalam kategori sedang, (4) faktor waktu sebanyak 4 responden atau 50% masuk ke dalam kategori kurang efektif.Â Kata kunci : faktor penghambat, pelaksanaan program pengayaan, program pengayaanÂ